2010
DOI: 10.1097/mpg.0b013e3181cd26f9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gestational Age, Cesarean Section, and Type of Feeding on Fecal Human β‐Defensin 2 and Tumor Necrosis Factor‐α

Abstract: : Low fecal HBD-2 may be a risk factor in preterm infants to develop neonatal enteric disease, such as necrotizing enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
4
20
1
3
Order By: Relevance
“…Moreover, in our study, these reports also demonstrated positive correlation of amniotic hBD2 levels with premature rupture of membranes and microbial invasion of the amniotic cavity (25,26). During the first 2 wk of life, fecal hBD2 concentrations dropped, reaching a nadir at ~2 wk and slowly increasing from there on showing a similar postnatal dynamic as in two previous smaller studies (9,27). Concentrations of fecal hBD1 were similarly high in meconium and dropped afterwards to a very low baseline in all patients, which is consistent with several studies demonstrating the developmental regulation of hBD1 with almost no expression before 24 wk of gestational age (28,29).…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 73%
See 3 more Smart Citations
“…Moreover, in our study, these reports also demonstrated positive correlation of amniotic hBD2 levels with premature rupture of membranes and microbial invasion of the amniotic cavity (25,26). During the first 2 wk of life, fecal hBD2 concentrations dropped, reaching a nadir at ~2 wk and slowly increasing from there on showing a similar postnatal dynamic as in two previous smaller studies (9,27). Concentrations of fecal hBD1 were similarly high in meconium and dropped afterwards to a very low baseline in all patients, which is consistent with several studies demonstrating the developmental regulation of hBD1 with almost no expression before 24 wk of gestational age (28,29).…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 73%
“…Mortality rate of severe NEC was 66% (n = 4) with no further deaths in the remaining patients. A total of 732 fecal samples were available (mean 11 per individual, range [5][6][7][8][9][10][11][12][13][14].…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with the observation of unusually low fCP concentrations in fulminant NEC, this might indicate an impaired recruitment of granulocytes in the gastrointestinal lumen which could make these infants at risk for aberrant postnatal microbial colonization and subsequent NEC. Whereas several studies have already demonstrated a generally impaired immune response in VLBW infants [22,23,24], this idea is also supported by a recent study specifically demonstrating low fecal concentrations of the antimicrobial peptide hBD2 in premature infants [25] which also functions as a chemotactic factor for human neutrophils [26]. …”
Section: Discussionmentioning
confidence: 50%